PERAN SOCIAL SKILL TRAINING DALAM MENINGKATKAN KETERAMPILAN SOSIAL PASIEN SKIZOFRENIA KATATONIK - Muhammad Febrian Al Amin (Universitas Islam Indonesia, 2019)
This study aimed to determine the role of social skill training in improving social skills. Data collection methods used in this study are interviews, WAIS testing, projective test, and SSCT. The subject of the study was an 18 years old male who had a catatonic schizophrenic disorder who did not want to interact socially before entering Menur Psychiatric Hospital. The intervention given was Social Skill Training to improve social skills in 7 sessions. Through Social Skill Training, subjects are trained in various social skills, such as greeting, introducing themselves, communicating lightly and to make friends so that the subject is no longer to be silent and sculpting in the room and make the subject be able to go to school again. The results showed a number of changes, such as subjects who were able to greet, introduce themselves first, even able to have small conversations with people around the subject.